Evolution of physical characteristics from 2010 to 2022 in the England women's cricket team - Durrant, I.; Wedatilake, T.; Warren, A.; Callaghan, S. J.; Osguthorpe, D.; Harland, A.; Howe, L. P.; Tallent, J. (International Journal of Sports Science & Coaching, 2025)
The present study aimed to investigate the changes in the physical profile of the England women's cricket team over a 13-year period. Physical profiles of 45 female players were retrospectively analysed from 2010 to 2022. Mixed linear modelling was employed to examine changes in various physical parameters including 10 m and 20 m sprints, countermovement jump (CMJ) height, aerobic fitness (measured through the Yo-Yo intermittent recovery test level 1, Yo-Yo-IR1), and push and pull strength endurance across time. There was a significant increase in Yo-Yo IR1 performance over time (P < 0.001), with the distance covered improving from 1077 metres in 2011 to 1666 metres in 2014. Both 10 m (P < 0.001) and 20 m (P < 0.001) sprint times significantly improved up to 2014. Furthermore, there were significant increases in push (P < 0.001) and pull (P < 0.001) strength endurance across time. However, no significant changes were observed in run-2 performance. Although there were significant changes (P < 0.001) in CMJ height across time, no clear trends were evident for year-to-year changes. Overall, the study demonstrated a significant physical evolution of the England Women's Cricket Team over 13 years, characterised by high aerobic fitness and upper body strength endurance. Future physical development should therefore focus on developing speed and change of direction qualities.